Feasibility analysis of micro hydro plant at nawangan village of pacitan district - Diana Dellariam Bayu; Rintis Hadiani; Solichin Solichin (Universitas Sebelas Maret, 2017)
Nawangan Village of Pacitan District utilizes Kedung Pasang Micro Hydro Plant (MHP) as a power source, but the existing electricity power unable suffice the demand so it needs revitalization by calculating the new unit price and debit because of the previous reference already invalid. The problem is that the investment required for the construction of the MHP must provide benefits for a certain period. This study analyzed the ratio of power and energy potential of MHP with changes in pipe diameter and speed of existing turbines, and calculated the cost. The available power is currently at 112.5 kW and energy is 82150.66 kWh. The results of the analysis show that the power increase can be done up to 142,95 kW a year or equivalent 218%, the energy can be done up to 139.427 kWh a year, meanwhile the benefit is Rp44.566.169, increase Rp26.604.588,- from existing condition or equivalent 148,1% which is done by changing the diameter of penstock and the turbine. Economic analysis of Kedung Pasang MHP development plan shows NPV of Rp6.717.110,- that is greater than 0, the value of IRR is 11% greater than the interest rate set by Bank Negara Indonesia 46 of 10,25% and BCR value of 1,19 is greater than 1, thus the revitalization of Kedung Pasang MHP feasible to be implemented.